A Minecraft movie. Welcome to the Overworld! - Shealy, Dennis R, 1969- (New York : Random House, 2025)
Henry and his friends find adventure--and danger--when they enter the mysterious Overworld!
K-3
Keywords: Minecraft (Game) -- Juvenile fiction; Video game characters -- Juvenile fiction; Video games -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Minecraft (Game) -- Fiction; Video game characters -- Fiction; Video games -- Fiction; Adventure and adventurers -- Fiction; Action and adventure fiction; Readers (Elementary)